Cost of Illness Analysis and the Impact of JKN Utilization on Patients with Type 2 Diabetes Mellitus - Munawarah, Vivi Ridha; Gurning, Fitriani Pramita; Aidha, Zuhrina (Indonesian Journal of Global Health Research, 2024)
Globally, diabetes is a major public health problem in developing countries due to its chronic nature, rapidly increasing prevalence, complications, and need for long-term care. Cost of Illness aims to estimate the impact of a particular disease in terms of quality of life and economic costs. Objective: This study aims to determine the cost of illness and the impact of JKN utilization in reducing the economic burden on patients with type 2 diabetes mellitus based on the perspective of outpatients at Puskesmas Talun Kenas. Method: This study is a type of quantitative research with a comparative approach. The sampling technique used purposive sampling technique, using the Lemeshow formula so that 100 samples were obtained. Results: The results showed that the total Cost Of Illness for one treatment visit using JKN was IDR 2,990,000 with an average of IDR 45,303. While the total Cost Of Illness for type 2 diabetes mellitus sufferers who seek treatment in general is IDR 3,805,000, - with an average value of IDR 111,911, - for one treatment visit. The results of the t-test obtained the value of the two groups had a significant difference in COI, namely p = 0.0. Conclusions: the total cost of illness of type 2 diabetes mellitus patients who seek treatment using JKN is significantly smaller than that of type 2 diabetes mellitus patients who seek treatment with independent payment. So that the utilization of JKN has an impact on reducing the economic burden of patients with type 2 diabetes mellitus at Puskesmas Talun Kenas.